Modified Charles procedure and lymph node flap transfer for advanced lower extremity lymphedema. Issue 6 (14th February 2014) - Sapountzis, Stamatis; Ciudad, Pedro; Lim, Seong Yoon; Chilgar, Ram M.; Kiranantawat, Kidakorn; Nicoli, Fabio; Constantinides, Joannis; Wei, Matthew Yeo Sze; Sönmez, Tolga Taha; Singhal, Dhruv; Chen, Hung‐Chi
<x xml:space="preserve">Abstract</x> Introduction Treatment of advanced lymphedema remains a challenge in reconstructive surgery. Microsurgical techniques seem to be effective in early stage lymphedema, however in advanced stages their role is not well established. In this study, we present a novel approach for advanced lymphedema combining excisional procedure (Charles) with transferring lymph node flap. Patients and method From 2010 to 2013, 24 patients (18 women, six men, mean age 53 years old) presented with late stage of lower extremity lymphedema. The modification of Charles procedure consisted of preserving the superficial venous system of the dorsum of the foot and the lesser saphenous vein, which were used for the venous anastomosis of the transferred lymph node flap. In 11 patients we transferred the inguinal lymph node flaps from the contralateral site, meanwhile in 13 patients supraclavicular lymph node flaps were used. Results Maximum reduction of the lymphedema was achieved. No major complication was detected postoperatively. There were two patients with partial loss of the skin graft necessitated re‐grafting. All the lymph node flaps survived well. The patients resumed normal daily activities within a period of 2 months. The mean follow‐up was 14 months (3–26 months). During this period, no recurrence of the lymphedema was observed. Conclusion The combination of the modified Charles procedure with vascularized transferring of lymph node flap is an effective method for treatment of advanced stage lymphedema. © 2014 Wiley Periodicals, Inc. Microsurgery 34:439–447, 2014.